Nitrogen Fertilizer Timing and Phosphorus and Potassium Fertilization Rates for Established Endophyte-Free Tall Fescue - D. W. Sweeney; J. K. Farney; J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2020)
Tall fescue production was measured during the second year of a study with locations started in fall of 2016 and fall of 2017. In the second year at both sites, phosphorus (P) fertilization rate did not affect harvest yields. Applying nitrogen (N) in late fall or late winter resulted in greater spring yields than applying N in spring or not applying N. However, fall harvest yields at Site 1 in 2018 were greater without N, but were greater with spring N application at Site 2 in 2019. In both site-years, the second-year tall fescue total yield rank as affected by N fertilizer timing was late fall=late winter>spring>no N, even though overall yields were greater in 2019 at Site 2.
Keywords: tall fescue; yield; phosphorus; potassium; rates